Incidence and risk factors for feline lymphoma in UK primary‐care practice. (15th December 2020) - Economu, L.; Stell, A.; O'Neill, D. G.; Schofield, I.; Stevens, K.; Brodbelt, D.
Abstract : Objectives: The study aimed to estimate the incidence and prevalence of feline lymphoma in cats attending primary‐care practices across the UK and to identify patient‐based and environmental (radon and pesticide exposure) risk factors. Materials and Methods: Case records from the VetCompass programme from primary‐care veterinary practices in the UK were searched for a diagnosis of lymphoma in cats in 2016. Cases were required to have had an external laboratory confirmed diagnosis based on cytology and/or histopathology. A nested case–control study design was used to identify risk factors for lymphoma using multivariable logistic regression. Results: From a cohort of 562, 446 cats under veterinary care at VetCompass participating practices in 2016, a total of 271 lymphoma cases were identified (prevalence: 48/100, 000, 95% confidence interval (CI) 44 to 56/100, 000; incidence 32/100, 000, 95% CI 26 to 35/100, 000). There were 180 incident lymphoma cases and 803 controls, all aged 2 years and older. Male (odds ratio (OR) 1.7, 95% CI 1.2 to 2.4), insured (OR 3.6, 95% CI 2.3 to 5.6) and older cats (compared to cats 2 to <5 years, OR 5.0, 95% CI 2.8 to 8.8) were associated with increased odds of lymphoma diagnosis. Vaccinated cats were associated with decreased odds (OR 0.7, 95% CI 0.5 to 1.0) compared to unvaccinated cats, although the type of vaccination received was not statistically significant. Breed and environmental factors studied were not associated with a diagnosis of lymphoma. Clinical Significance: This is the first study to estimate the frequency and report risk factors for lymphoma in cats attending UK primary‐care practice.